The aspherical explosion of the Type IIP SN 2017gmr. (5th September 2019) - Nagao, T; Cikota, A; Patat, F; Taubenberger, S; Bulla, M; Faran, T; Sand, D J; Valenti, S; Andrews, J E; Reichart, D E
ABSTRACT: Type IIP supernovae (SNe IIP), which represent the most common class of core-collapse (CC) SNe, show a rapid increase in continuum polarization just after entering the tail phase. This feature can be explained by a highly asymmetric helium core, which is exposed when the hydrogen envelope becomes transparent. Here we report the case of an SN IIP (SN 2017gmr) that shows an unusually early rise of the polarization, ≳30 d before the start of the tail phase. This implies that SN 2017gmr is an SN IIP that has very extended asphericity. The asymmetries are not confined to the helium core, but reach out to a significant part of the outer hydrogen envelope, hence clearly indicating a marked intrinsic diversity in the aspherical structure of CC explosions. These observations provide new constraints on the explosion mechanism, where viable models must be able to produce such extended deviations from spherical symmetry, and account for the observed geometrical diversity.